Vignette Technique and its Applications in Teacher Education - Kaya, Zehra; Kaya, Osman Nafiz (Turkish Education Assoc, 2013)
Stories that have been used frequently in many studies in social sciences, including educational research, are categorized in four different types as follows: case studies, case stories, scenarios, and vignettes. In literature, the vignette has been frequently used incorrectly or interchangeably with other types of stories. The purpose of this study is to describe what vignette is as a technique, phases of creating a vignette, educational benefits and limitations of vignettes by using various examples of vignettes in order to guide researchers in the field of teacher education. In particular, the benefits of vignette technique as a data collection tool, instructional and assessment approaches, and how vignette technique has been integrated with technology in teacher education studies are discussed based on the findings of pertinent literature during the last decade.
Ögretmen e?itiminde vignette tekni?i ve uygulamalari
Keywords: Stories; vignette technique; teacher education